Manganese in the system soil-plant: Phytoremediation aspects - Aleksandra D. Papludis; Slađana Č. Alagić; Snežana M. Milić (Zaštita Materijala)
Althought manganese (Mn) is not recognized as a metal that contaminate soil in some significant extent, its concentrations have reached very high levels in some regions of the World. As one of effective methods for Mn removal, the method of phytoremediation can be considered. This method uses natural plant capabilities for metal stabilization in the soil, or for metal extraction and further accumulation in the tissues. Plants that have hyperaccumulation capabilities are of special interest for phytoremedition, so that, in this paper, numerous specifics related to Mn behavior in the system soil-plant are represented, with special accent in regard to hyperaccumulation.